HIGHER EDUCATION IN INDIA: HISTORY, GROWTH AND DEVELOPMENT - Devi, Pallabi (International Journal of Psychosocial Rehabilitation, 2020)
India is a rapidly developing democratic country. Development of human resource in a country depends upon the quality of education prevailing in the country. Higher education imparted the education through colleges and universities. Over the last two decades, higher education in India makes remarkable transformation with well planned expansion of education. Now India has increased its enrollment numbers with improved teaching learning materials. But fostering quality teaching depict the institutions of higher education must offer that kind of education which fulfill the expectations and requirement of the students in present day context. Education in Ancient India means the education that prevailed before the coming up of the present system of modern education introduced by the British. India starts its higher education through Nalanda, Vikramshila, Vallabhi and Takshashilla which also imparted religious education and philosophy, though Takshashilla also gives imparted in professional education. Ancient Indian civilization has the most prominent place in the civilization of the world. The education system in ancient India plays an important role to transfer of oral and written tradition to one generation to next. In Vedic period, the intellectual equipment and efficiency were the corner stone of human progress. In Vedic period every person should go for their study which is known as Brahmacharya during the childhood and adolescence. In the medieval centuries (12th -18th) India played a major phase of social and cultural synthesis which emphasized the interaction between new settlers from Central and Western Asia and on the other hand the early inhabitants of the sub-continent. There were some important South Indian Education Centers where Brahmin teachers along with scholars devoted their entire lives to study Vedas, Shastras and the Purans. These were Cholla, Pandaya, in the Vijayanagar Empire, Varanasi, Hardwar, Nadia and Ujjain etc. In Northern India, Madras’s were the centre of higher learning. These were provided secular studies, but also took care of the religious and moral training of the students. Sanskrit and Arabic higher learning also included secular and scientific learning in law, medicine, mathematics, astronomy, literature, philosophy and theology.